PERAN NEGARA DAN AGAMA DALAM MEMERANGI TERORISME - Qodir, Zuly (Jurnal Orientasi Baru, 2012)
Terror movements are motivated by psychological, economic, cultural, politics and religious problems. This is a complex problem. But, it becomes more sensitive when religious motivation is involved in it. Nevertheless, terrorism is a human problem that urges all people and the institutions of the state and religions to discover solutions. As in Indonesia, all people are both citizens and members of religions, it is important to realize and get a concrete way against terrorism. What then is the role of religions and the state to overcome the problem of terorrism? How do religions and the state actualize their role against terrorism? Overcoming the problem of terrorism is the first step for developing a peaceful social life. The following step is to promote humanity. However, the state and religions have the same responsibility in educating all people to live universal values such as fraternity, peace, justice, and reciprocal respect and help as way of life.